Cryogenic Resources: Ice, Snow, and Permafrost in Traditional Subsistence Systems in Russia - Roman Fedorov (Resources, 2019)
This article is devoted to the study of the role of natural cryogenic resources in the traditional subsistence systems of the people of Russia. The main source of the actual information and the empirical basis reflecting the features of traditional ecological knowledge of the ethnic groups considered in the article are the scientific publications and ethnographic descriptions made by Russian researchers in the second half of the 19th century through to the beginning of the 21st century, and the results of our modern field research in the territory of Siberia and the Far East of Russia. The methodology of the study lies in the field of ethnoecology, and contains comparative and typological approaches, which have allowed for the detection and systematization of the main spheres of using natural cryogenic resources in traditional subsistence systems by the people of Russia, which include using the environment for indigenous subsistence, building materials, food preservation, obtaining potable water, the irrigation of crops, etc. In conclusion, some of the prospective for the ethnoecological examination of the role of the natural cryogenic resources in traditional subsistence systems were designated, and adaptations to modern innovative technologies based on the rational use of natural resources were also examined.